2015
DOI: 10.1515/intag-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted Effects of Biochar on Maize Growth and N Use Efficiency Depending on Soil Conditions

Abstract: Biochar amendment may improve crop growth through its nutrients and indirect fertility. However, this improvement varies in a wide range of biochars, crops, and soils. Our objectives were to determine the response of crop growth to biochar amendment and to assess the N use efficiency relative to the biochar and the soil types. In this pot experiment, we investigated five typical agricultural soils in China amended with two biochars. Four treatments were designed: the soil itself as a control, the soil amended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Studies have shown that deriving an appropriate N-recovery index (%) could be used as an indicator for evaluating applied fertilizer use efficiency (Agegnehu et al 2016). Previous studies reported 75% increase in maize biomass relative to NPK fertilizer alone when biochar and NPK fertilizer were combined at different ecological zones in southern China (Zhu et al 2015). Studies by Gathorne-Hardy et al (2009) also reported over 30% increase in barley yield when biochar and N fertilizer were co-applied.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that deriving an appropriate N-recovery index (%) could be used as an indicator for evaluating applied fertilizer use efficiency (Agegnehu et al 2016). Previous studies reported 75% increase in maize biomass relative to NPK fertilizer alone when biochar and NPK fertilizer were combined at different ecological zones in southern China (Zhu et al 2015). Studies by Gathorne-Hardy et al (2009) also reported over 30% increase in barley yield when biochar and N fertilizer were co-applied.…”
Section: Introductionmentioning
confidence: 99%
“…Although many reports of biochar addition resulting in improved crop yields have been reported, some studies have described contradictory negative results for specific soil conditions [14], with improvements in soil quality affording no improvements in crop growth yields. Jeffery et al (2017) reported that biochar addition is most likely to benefit agriculture in low-nutrient, acidic soils that are present in the tropics [15].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar further has lower N content and high compositional variability dependent upon the conditions of pyrolysis and feedstock utilized [36] [37]. Biochar effects may also prove to be soil specific [38]. To date, biochar utilization has been predominately focused in biocoal, syngas, bio-oil, and hydrothermal production of biomass under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, biochar utilization has been predominately focused in biocoal, syngas, bio-oil, and hydrothermal production of biomass under anaerobic conditions. Ultimately, biochar application to soils is dependent upon parent material, temperature rates, and application rates [36] [37] [38] [39].…”
Section: Introductionmentioning
confidence: 99%